A Glimpse of Satellite Galaxies in the Milky Way with the 2.5 m Wide Field Survey Telescope (WFST): Boötes III and Draco - Chao Yang; Zhizheng Pan; Min Fang; Xian Zhong Zheng; Binyang Liu; Guoliang Li; Tian-Rui Sun; Ji-An Jiang; Miaomiao Zhang; Zhen Wan; Shuang Liu; Han Qu; et al. (The Astrophysical Journal)
We carry out deep imaging of the Milky Way satellite galaxies, Boötes III and Draco, with the Wide Field Survey Telescope (WFST) as one pilot observing program to demonstrate the capability of WFST. Combining catalogs with PS1 DR2 and Gaia DR3, we derive proper motions for candidate member stars in these two satellite galaxies over a 12 yr time baseline, yielding uncertainties of ∼1.8 mas yr ^−1 at 21 mag and ∼3.0 mas yr ^−1 at 22 mag in the r band. The proper motions derived from bright and faint stars are consistent, indicating no significant variation in proper motion across stellar luminosity as these galaxies undergo tidal interactions with the Milky Way (MW). Meanwhile, we suggest that Boötes III represents the bound remnant of the progenitor galaxy that gave rise to the Styx stream, as evidenced by its elongated density profile and overdensity in both spatial and kinematic space. This is the first paper to use WFST to measure the proper motions of faint stars in MW satellite galaxies. More detailed analyses will be presented in forthcoming papers from the wide field survey program.